Reversibility and β-sheet formation are decoupled in tau condensate aging - Charlotte M. Fischer; Irina A. Edu; Tomas Sneideris; Ieva Baronaite; Zenon Toprakcioglu; Leif-Thore Deck; Daoyuan Qian; Rob Scrutton; Lasse Dreyer; Jitao Wen; Daniel E. Otzen; Si Wu; et al. (Proceedings of the National Academy of Sciences, 2026)
Neurofibrillary tangles (NFTs) formed from the protein tau disrupt neuronal function in Alzheimer’s disease and are strongly associated with cognitive decline. Early events in tau aggregation are increasingly linked to the formation of biomolecular condensates, which lower the energetic barriers to pathological aggregation by acting as intermediates that transition into insoluble assemblies, a mechanism also implicated in other neurodegenerative diseases, such as amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Despite growing evidence for this pathway, the molecular basis by which reversible condensates evolve into irreversible, pathogenic aggregates has remained unclear. Here, we map the phase behavior, structural transitions, and thermodynamic reversibility of tau during condensate aging. Our results reveal that the two hallmark features of the pathological end state, β-sheet enrichment and irreversible aggregation, emerge at different rates and occupy distinct regions of the phase space, indicating that these properties are mechanistically uncoupled. Notably, we identify tau condensate phases that are β-sheet rich yet thermodynamically reversible, as well as irreversible intermediates that lack β-sheet structure. These findings expand the landscape of tau aggregate species beyond a simple linear progression toward fibrils and highlight a diverse array of intermediates with distinct structural and thermodynamic properties. This decoupling of structure and irreversibility has important implications for understanding tau aggregation mechanisms and may offer targets for therapeutic intervention.